Charting New Imaginaries for DEI: Lessons from a Capabilities Approach to Justice - Deryl K. Hatch-Tocaimaza; Ruth Oliver Andrew (Education Sciences, 2025)
In the face of ongoing debate surrounding diversity, equity, and inclusion (DEI) in higher education, this essay examines the limitations of current DEI frameworks by interrogating the theories of justice on which they are implicitly based. While DEI initiatives aim to address both the symptoms and structural roots of marginalization, they often fall short of realizing transformative change within entrenched institutional dynamics. This essay contends that the justice paradigms most commonly underpinning DEI—rooted in rights-based and utilitarian traditions prevalent in modern liberal institutions—fail to fully engage the conditions necessary for human freedom, flourishing, and self-determination. In response, it advances a capabilities approach to justice as a more expansive framework for understanding and guiding DEI efforts. Emphasizing individuals’ real freedoms to achieve well-being in context, the capabilities approach foregrounds the relational, material, and institutional dimensions of justice. Reframing DEI through this lens, the essay invites higher education professionals to engage in equity work that is not only compliant or symbolic but rooted in the transformation of the conditions that support human and ecological thriving. Rather than offering a definitive model, this intervention aims to animate new questions and practices that expand the horizon of what justice-oriented DEI work in higher education can become.